Gundelia siirtica (Asteraceae), a new lactiferous species from Siirt (south-eastern Anatolia) - Firat, Mehmet (Phytotaxa, 2019)
Gundelia siirtica sp. nov. is described from Siirt Province, Turkey. The new species appears to be most similar to G. mesopotamica and G. armeniaca, from which it differs in plant height and indumentum, size and number of synflorescences, colour of corolla externally and internally, shape and size of fruit complex (disseminule). A comprehensive description of this species is provided, with detailed photographs, a distribution map, a habitat description, a vernacular name and an IUCN conservation status.